The Role of Business Performance in Mediating Relationship between Triple Bottom Line and Business Survival - Asraf; Supriaddin, Nofal; Ningtyas , Sri Ayu (LifeSciFi, 2025)
This study investigates the influence of the Triple Bottom Line (TBL), comprising economic, social, and environmental dimensions, on business performance and business sustainability, with business performance functioning as a mediating variable. A quantitative research design was employed, collecting data from 208 business respondents through a structured questionnaire, which was then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that all three TBL dimensions have a significant impact on both business performance and sustainability, with the social dimension showing the strongest effect in enhancing performance and supporting business survival. Furthermore, business performance positively influences sustainability and serves as a significant mediator in the relationship between the social dimension and business survival, whereas its mediating role is not significant for the economic and environmental dimensions. Theoretically, this study contributes to the literature by emphasizing the critical role of business performance as an intermediary mechanism within the TBL framework, particularly in relation to the social dimension. Practically, the results suggest that business actors should focus on social-oriented strategies, such as improving employee satisfaction, ensuring fair compensation, and empowering communities, to strengthen sustainability. Additionally, the study offers recommendations for policymakers to facilitate and support sustainable business practices among small and medium enterprises.